Pengembangan perangkat layanan bimbingan klasikal untuk meningkatkan tanggung jawab belajar siswa sekolah menengah pertama - Setiani, Ni Kadek Dewi; Gading, I Ketut; Lestari, Luh Putu Sri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research is a development research (research & development). A Classical Guidance Service Toolkit to Increase Student Learning Responsibilities is the finished product. The 4D model put forth by Thiagarajan (1974) is used in this study's development, which goes as follows: Define, design, develop, and distribute are the first three steps. Five guidance and counseling professionals, including three professors at FIP Undiksha and two counseling teachers at SMP Negeri 2 Singaraja, participated in this study. Examples of classical guide service instruments include evaluation tools, service materials, media, and RPL. The findings of the CVR index calculation using the overall score yielded a CVR of 65 upon acceptance of the classical guiding service device, yielding a CVI calculation result of 1. As can be seen the t-test probability value or Sig.(2-tailed) on the table is 0,023 this value is less than 0.05 significance level. The classical guidance service tool is hence successful in raising student learning responsibility. Thus, increasing student learning responsibility is successful with the typical guidance service tool